Comparison of the CT-based micromotion analysis method versus marker-based RSA in measuring femoral head translation and evaluation of its intra- and interobserver reliability: a prospective agreement diagnostic study on 27 patients up to 1 year - Vasileios Angelomenos; Bita Shareghi; Raed Itayem; Maziar Mohaddes (Acta Orthopaedica)
Background and purpose: Computed tomography radiostereometric analysis (CT-RSA) assesses implant micromovements using low-dose CT scans. We aimed to investigate whether CT-RSA is comparable to marker-based radiostereometric analysis (RSA) measuring early femoral head migration in cemented stems. We hypothesized that CT-RSA is comparable to marker-based RSA in evaluating femoral head subsidence. Methods: We prospectively included 31 patients undergoing cemented total hip arthroplasty (THA), of which 27 were eligible for the analysis. Femoral head migration at 1 year was measured with marker-based RSA and CT-RSA. Comparison was performed using paired analysis and Bland–Altman plots, and the intra- and interobserver reliability of CT-RSA was assessed Results: The median (interquartile range [IQR]) translation on the Y-axis measured with marker-based RSA was –0.86 mm (–1.10 to –0.37) and –0.83 mm (–1.11 to –0.48) for CT-RSA (i.e. subsidence), with a median difference of –0.03 mm (95% confidence interval [CI] –0.08 to 0.18). The minimal important difference in translation was set to 0.2 mm. This value was excluded from the CI of the differences. No statistical difference was found between marker-based RSA and CT-RSA regarding assessment of subsidence of the femoral head. The Bland–Altman plots showed good agreement between the 2 methods in measuring subsidence of the femoral head. The intra- and interobserver reliability of the CT-RSA method was excellent with intraclass correlation coefficient (ICC) = 1 (0.99–1) and ICC = 0.99 (0.99–1), respectively. Conclusion: We showed that CT-RSA was comparable to marker-based RSA in measuring femoral head subsidence. Moreover, the intra- and interobserver reliability of the CT-RSA method was excellent, suggesting that the method is assessor independent.